Inhibition of free fatty acid formation in oil palm fruit by using buffer solution - Ainul Farhani, Ahmad Nizam (2021)
Free fatty acid (FFA) is one of the indicators commonly used in evaluating palm oil quality. It is produced from the hydrolysis reaction of triglyceride (TG), the main constituent of palm oil, and the presence degrades the oil quality due to rancidity. The allowable limit of FFA in crude palm oil (CPO) is 5% wt; otherwise, it will be removed during refinery and be regarded as oil losses. Current method in controlling the FFA formation is by sterilization of fresh fruit bunches (FFBs) at high temperature and pressure. However, due to the closed-packed arrangement of FFBs, heat may not uniformly be distributed, causing incomplete inhibition of FFA. To observe a realistic FFA trend in oil palm mills, the effects of FFBs storage method on hydrolysis by mesocarp lipase in oil palm fruits were studied as well, for a week. Besides that, this study aims to enhance the FFA reduction by applying two types of buffer solution before the digestion step. Factors that are likely affecting the reaction were studied using the factorial design by analyzing the FFA concentration difference. These include buffer concentration whereby the ranges is 1–10 mM for acetate or 1–20% w/v for sodium silicate, buffer loading from 10 to 250 ml per 100 g and digestion time between 35 to 60 minutes. FFA content from outdoor samples contradicts the increased oscillatory trend shown by indoor samples. The indoor samples generally show an increasing trend as expected. The models were best fitted into damped sine equation whereby the R2 values for 2003, 2007 and 2015 are 0.95, 0.62 and 0.84, respectively. Meanwhile, the outdoor samples show the downward trend of FFA and were fitted into sigmoidal and damped sine equations. The R2 values are 0.48, 0.89 and 0.77, respectively. However, both methods' glyceride content increased in exponential rise or power after a week suggesting moisture as a limiting reactant. There was no conclusive trend in oil and FFA contents based on the age of the oil palm tree. For second objective, acidic or basic buffer had been applied on the palm mesocarp to compare the FFA content in both sample and blank. Overall, positive effects on FFA inhibition by buffer solutions were observed. The models are significant in which the R2 values for acetate buffer is 0.85 while for sodium silicate, the R2 is 0.88. Acetate buffer at 1 mM concentration had strongly affected the FFA formation by reducing up to 14% v/v. Although the buffer concentration alone was not significant for sodium silicate buffer, the interaction between buffer concentration and buffer loading had significantly reduced the FFA formation in which around 30% v/v difference was achieved. These were concluded based on three basic principles: lipase deactivation due to extreme pH conditions, maintaining the equilibrium reaction by adding extrinsic carboxylic acid and neutralization of FFA by using a basic solution. The use of buffer solutions in palm oil mill potentially reduces the oil losses during the refinery. However it is suggested to have further investigation to delineate the presence of any other by-products in the extract.